Hubungan Agama dan Pengetahuan Pasca Runtuhnya Rezim Sains Modern - Mujahidin, Anwar (KALAM, 2013)
Modern age is marked by the progress of humans reasoning as rational beings. Science is growing rapidly with avariety of scientific methodology that guarantees the truth findings. In contrast, Beliefs and religious truth are assessed naïve and subjective, and all non-rational-minded communities are regarded as primitive, uncivilized society. This phenomenon brings the tension in the relation between religion and science and incites the two to negate and degrade each other existence. This article seeks to analyse the dialectical relationship between religion and science in the realm of ontology and epistemology that has lasted a long time. The goal is to obtain a new horizon for the future relation between science and religion. From the ontological and epistemological perspectives, the conflict does not really have a solid foundation as religion is not dealing with spiritual issues, mystical, or non-rational an sich. In fact, religion can be studied scientifically with the appropriate methodological foundation and objective. Likewise, a review of religion can be built on scientific approach. Through this perspective, the relationship between religion and science is no longer diametric, but interdisciplinary dialectic that mutually enrich and strengthen each other.